Tropical stream ecology (Elsevier, 2008)
This book describes the main features of tropical streams and their ecology. It covers the major physico-chemical features, important processes such as primary production and organic-matter transformation, as well as the main groups of consumers: invertebrates, fishes and other vertebrates. Information on concepts and paradigms developed in north-temperate latitudes and how they do not match the reality of ecosystems further south is expertly addressed. The pressing matter of conservation of tropical streams and their biodiversity is included in alomost every chapter, with a final chapter providing a synthesis on conservation issues. For the first time, Tropical Streams Ecology places an important emphasis on viewing research carried out in contributions from international literature